Analisis Penyebab Nyeri dan Ketidaknyamanan dalam Bekerja pada Pengrajin Keset Kain Limbah–Pringapus Semarang - Zuraida, Rida (ComTech: Computer, Mathematics and Engineering Applications, 2012)
This research identified any kind of work condition and craftsman’s posture that trigger the pain and discomfort for craftsman of doormat in Pringapus, Semarang. Observation of the work condition is conducted including work facilities and their posture during sewing process. To identify their pain and discomfort, Nordic Musculoskeletal Questionnaire (NMQ) is used as reference. The result is used as an input for rapid upper limb assessment worksheet (RULA) to determine the level of the risk. RULA’s final score is indicated the conditions need further investigation and change may be needed. Based on the analysis using fishbone diagram, to overcome pain/discomfort in the area of the neck and the shoulder, high adjustment of table and seat is suggested, because the evidence shows they trigger the craftsmen’s bad posture. For pain/discomfort of back and waist, the seat should have good back support. Whereas for the hip, the craftsman suggested to use the seat with thick and wider sleeper, so they can sit comfortably. For foot problems, to relieve the pain for their free feet, it is suggested to use a bench that functions as foot rest; and for the sewing feet, it is suggested to give heels support so the sewers' heels can be free from strain while sewing.